Choledochal cyst of the cystic duct - A supplement to todani's classification - Mehak Sehgal; Devendra Kumar Yadav; Devasenathipathy Kandasamy; Minu Bajpai; Vishesh Jain; Anjan Kumar Dhua; Prabudh Goel (Wolters Kluwer Medknow Publications, 2021)
Choledochal cyst of the cystic duct is a rare anomaly; broadly classified, the pathology may either present as a solitary anomaly or with concomitant involvement of other parts of the biliary tree. In the absence of standard guidelines for surgical planning, the definitive management is based on the experience shared in the literature in the form of case reports and case series. The available options should be discussed with the patient while explaining the possible short- and long-term complications. The authors herewith present two cases of choledochal cyst of the cystic duct along with a review of literature relevant to their etiopathogenesis and its implications for the definitive management.